Conference on Lasers and Electro-Optics 2020
DOI: 10.1364/cleo_qels.2020.fm4c.6
|View full text |Cite
|
Sign up to set email alerts
|

Position and Frequency Control of Strain-induced Quantum Emitters in WSe2 Monolayers

Abstract: By integrating WSe2 monolayers with a nanopatterned Si micro-cantilever, we create the quantum emitters at deterministic sites and control their frequency with voltages. Also, reduction of the fine-structure splitting is observed by engineering the strain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…Such structures dramatically improve the brightness of solid-state quantum emitters with enhanced light extraction [39,40], and also improve the collection efficiency and generation rate of single photons by far-field engineering [33,41], and Purcell enhancement [42,43]. Furthermore, researchers are continually developing techniques for controlling the emitters' position [44,45], frequency [46][47][48], and dephasing [28] [40], which have brought solid-state quantum emitters to the forefront of quantum light sources. Comprehensive reviews on solid-state emitters and important developments can be found in Ref.…”
Section: Solid-state Quantum Emittersmentioning
confidence: 99%
See 2 more Smart Citations
“…Such structures dramatically improve the brightness of solid-state quantum emitters with enhanced light extraction [39,40], and also improve the collection efficiency and generation rate of single photons by far-field engineering [33,41], and Purcell enhancement [42,43]. Furthermore, researchers are continually developing techniques for controlling the emitters' position [44,45], frequency [46][47][48], and dephasing [28] [40], which have brought solid-state quantum emitters to the forefront of quantum light sources. Comprehensive reviews on solid-state emitters and important developments can be found in Ref.…”
Section: Solid-state Quantum Emittersmentioning
confidence: 99%
“…Within a hybrid system, this can be achieved by integrating the emitters on miniaturized piezoelectric actuator chips so that the platform can induce a local strain to individual emitters in an array [Fig. 7(d)] [46][47][48].…”
Section: B Generation Of Multiple Indistinguishable Single Photonsmentioning
confidence: 99%
See 1 more Smart Citation
“…3(b)), with purities reaching as high as 95% and detection rates up to 10 kHz; however, a withstanding challenge was that emitters were still appearing in a large spectral range of 720-800 nm, and also, these emitters were limited to cryogenic temperatures. Other strain-engineering methods have been explored following these demonstrations, such as metallic nano-cubes 42 and nano-particles 43 , nano-indentation with AFM tips 44 , and electrically controlled microcantilevers 45 . While each of these approaches have advantages, such as dynamical control over the extent of strain 45 or concurrently achieving Purcell enhancement 42,43 , overall, the emitters' purities were not comparable to nano-pillar approaches 31,32 .…”
Section: A Engineering Of Spesmentioning
confidence: 99%
“…Other strain-engineering methods have been explored following these demonstrations, such as metallic nano-cubes 42 and nano-particles 43 , nano-indentation with AFM tips 44 , and electrically controlled microcantilevers 45 . While each of these approaches have advantages, such as dynamical control over the extent of strain 45 or concurrently achieving Purcell enhancement 42,43 , overall, the emitters' purities were not comparable to nano-pillar approaches 31,32 . For each of these approaches to strain engineering, control over the SPE emission energy has not been demonstrated, and SPEs appear across a large distribution of energies.…”
Section: A Engineering Of Spesmentioning
confidence: 99%